Developing Triggers for Environmental Effects Monitoring Programs for Trout‐Perch in the Lower Athabasca River (Canada). (8th August 2019) - Kilgour, Bruce W.; Munkittrick, Kelly R.; Hamilton, Liza; Proulx, Catherine L.; Somers, Keith M.; Arciszewski, Tim; McMaster, Mark
Abstract: Baseline variations in trout‐perch energy use (growth, gonad size) and energy storage (condition, liver size) were characterized between 2009 and 2015 in 8 reaches of the Athabasca River (AB, Canada), including 2 reaches upstream of the city of Fort McMurray (AB, Canada) and 6 reaches downstream of Fort McMurray among existing oil sands operations. Generalized linear models, used to account for background variation, indicated that fork length, gonad size, and liver size decreased, whereas body weight increased, in relation to river discharge, for both male and female trout‐perch. Air temperature was positively correlated with liver size and negatively correlated with gonad size and body weight for females, but only positively correlated with gonad weight for males. These linear models explained approximately 20 to 25% of the variation in adjusted body size, and upward of 80% of the variation in adjusted body weight, liver weight, and gonad weight. Residuals from linear models were used to estimate normal ranges of variation for each of the fish population performance measures. Combined, the models and normal ranges can be used to assess subsequent monitoring data, providing potential triggers for follow‐up monitoring activities. Environ Toxicol Chem 2019;38:0–0. Environ Toxicol Chem 2019;38:1890–1901. © 2019 SETAC.